Identifying Early Inflammatory Changes in Monocyte-Derived Macrophages from a Population with IQ-Discrepant Episodic Memory - LYNCH, MARINA; MCDONALD, CLAIRE; ROBERTSON, IAN; BRENNAN, SABINA (My University, 2013)
Background Cells of the innate immune system including monocytes and macrophages are the first line of defence against infections and are critical regulators of the inflammatory response. These cells express toll-like receptors (TLRs), innate immune receptors which govern tailored inflammatory gene expression patterns. Monocytes, which produce pro-inflammatory mediators, are readily recruited to the central nervous system (CNS) in neurodegenerative diseases. Methods This study explored the expression of receptors (CD11b, TLR2 and TLR4) on circulating monocyte-derived macrophages (MDMs) and peripheral blood mononuclear cells (PBMCs) isolated from healthy elderly adults who we classified as either IQ memory-consistent (high-performing, HP) or IQ memory-discrepant (low-performing, LP). Results The expression of CD11b, TLR4 and TLR2 was increased in MDMs from the LP group when compared to HP cohort. MDMs from both groups responded robustly to treatment with the TLR4 activator, lipopolysaccharide (LPS), in terms of cytokine production. Significantly, MDMs from the LP group displayed hypersensitivity to LPS exposure. Interpretation Overall these findings define differential receptor expression and cytokine profiles that occur in MDMs derived from a cohort of IQ memory-discrepant individuals. These changes are indicative of inflammation and may be involved in the prodromal processes leading to the development of neurodegenerative disease.
PUBLISHED
Keywords: Alzheimer disease; Central nervous system; Cytokines Inflammation; Inflammatory diseases; Macrophages; Memory; Immunology, Inflammation & Infection